Rho-kinase inhibition blunts renal vasoconstriction induced by distinct signaling pathways in vivo - Cavarape, Alessandro; Endlich, Nicole; Assaloni, Roberta; Bartoli, Ettore; Steinhausen, Michael; Parekh, Niranjan; Endlich, Karlhans (Journal of the American Society of Nephrology, 2003)
ABSTRACT. In addition to intracellular calcium, which activates myosin light chain (MLC) kinase, MLC phosphorylation and hence contraction is importantly regulated by MLC phosphatase (MLCP). Recent evidence suggests that distinct signaling cascades of vasoactive hormones interact with the Rho/Rho kinase (ROK) pathway, affecting the activity of MLCP. The present study measured the impact of ROK inhibition on vascular F-actin distribution and on vasoconstriction induced by activation/inhibition of distinct signaling pathways in vivo in the microcirculation of the split hydronephrotic rat kidney. Local application of the ROK inhibitors Y-27632 or HA-1077 induced marked dilation of pre- and postglomerular vessels. Activation of phospholipase C with the endothelin ETB agonist IRL 1620, inhibition of soluble guanylyl cyclase with 1H-[1,2,4]oxadiazolo-[4,3-a]quinoxalin-1-one (ODQ), or inhibition of adenylyl cyclase with the adenosine A1 agonist N6-cyclopentyladenosine (CPA) reduced glomerular blood flow (GBF) by about 50% through vasoconstriction at different vascular levels. ROK inhibition with Y-27632 or HA-1077, but not protein kinase C inhibition with Ro 31-8220, blunted ETB-induced vasoconstriction. Furthermore, the reduction of GBF and of vascular diameters in response to ODQ or CPA were abolished by pretreatment with Y-27632. ROK inhibitors prevented constriction of preglomerular vessels and of efferent arterioles with equal effectiveness. Confocal microscopy demonstrated that Y-27632 did not change F-actin content and distribution in renal vessels. The results suggest that ROK inhibition might be considered as a potent treatment of renal vasoconstriction, because it interferes with constriction induced by distinct signaling pathways in renal vessels without affecting F-actin structure. E-mail: alessandro.cavarapedpmsc.uniud.it